Noncoding RNAs from tissue-derived small extracellular vesicles: Roles in diabetes and diabetic complications - Wenguang Chang; Mengyang Li; Lin Song; Suo Miao; Wanpeng Yu; Jianxun Wang (Elsevier, 2022)
Diabetes is a systemic disease, and its progression involves multiple organ dysfunction. However, the exact mechanisms underlying pathological progression remain unclear. Small extracellular vesicles (sEVs) mediate physiological and pathological signaling communication between organs and have been shown to have important regulatory roles in diabetes and its complications in recent years. In particular, the majority of studies in the diabetes-related research field have focused on the noncoding RNAs carried by sEVs. Researchers found that noncoding RNA sorting into sEVs is not random but selective. Both tissue origin differences and environmental variations affect the cargo of sEVs. In addition, the function of sEVs differs according to the tissue they derive from; for example, sEVs derived from adipose tissue regulate insulin sensitivity in the periphery, while sEVs derived from bone marrow promote β-cell regeneration. Therefore, understanding the roles of sEVs from different tissues is important for elucidating their molecular mechanisms and is necessary for the application of sEVs as therapeutic agents for diabetes treatment in the future. In this review, we summarized current studies on the mechanisms of noncoding RNA sorting into sEVs, as well as the research progress on the effects of sEVs from different tissue origins and noncoding RNAs in diabetes and diabetic complications. The knowledge of noncoding RNAs in sEVs will help us better understand the role of sEVs in the diabetes progression.